Vom Praktisch-Werden der Ethik in interdisziplinärer Sicht : Ansätze und Beispiele der Institutionalisierung, Konkretisierung und Implementierung der Ethik - Maring, Matthias [Hrsg.] (Schriftenreihe des Zentrums für Technik- und Wirtschaftsethikam Karlsruher Institut für Technologie. Hrsg. von Matthias Maring, 2015)
In the present volume ""ethics - getting practical: an interdisciplinary view"" will be dealt with approaches and examples of institutionalisation, concretion and implementation of ethics, but also the limits of getting practical of ethics will be shown. The following sciences are amongst others involved: media sciences, philosophy, psychology, social sciences, technical and engineering sciences, and economics.